Family Physicians Attaching New Patients From Centralized Waiting Lists: A Cross-Sectional Study. (August 2018) - Breton, Mylaine; Smithman, Mélanie Ann; Touati, Nassera; Boivin, Antoine; Loignon, Christine; Dubois, Carl-Ardy; Nour, Kareen; Lamoureux-Lamarche, Catherine; Brousselle, Astrid
Purpose: In response to more than 15% of Canadians not having a family physician, 7 provinces have implemented centralized waiting lists for unattached patients. The aim of this study is to analyze the association between family physicians' characteristics and their participation in centralized waiting lists.Methods: Cross-sectional observational study using administrative data in 5 local health networks in Quebec, between 2013 and 2015. All physicians who had attached at least 1 patient were included (n = 580). Multivariate linear regressions for the number of patients and proportion of vulnerable patients attached per physician were performed.Results: Physicians with more than 20 years of experience represented more than half of those who had participated in the centralized waiting lists and physicians in traditional primary care models represented more than 40%. Physicians' number of years of practice, primary care model, local health network, and the number of physicians participating in the centralized waiting lists per clinic influenced physicians' participation. Physicians with 0 to 4 years of experience and those practicing in network clinics were found to attach more patients. Practicing in a Centre Locaux de Services Communautaires (local community service center) was associated with attaching 19% more vulnerable patients compared with practicing in a Family Medicine Unit (teaching unit).Conclusion: Centralized waiting lists seem to be used by early career physicians to build up their patient panels. However, because of the large number of them participating in the centralized waiting lists, physicians with more experience and those practicing in traditional models of primary care might be of interest for future measures to decrease the number of patients waiting for attachment in centralized waiting lists.